Effect of Native AMF inoculation on Nutrient Composition, Uptake and Quality Attributes in Cassava - Mathew, Vinod; Punnen Kurien (JOURNAL OF ROOT CROPS, 2022)
Results of the potted cassava experiment conducted during the crop season of 2018 and 2019 to determine the influence of native AMF inoculation in cassava revealed that inoculation of Glomus fasciculatum (AMF culture No 3) with P nutrition at 100 per cent combined with application of N and K at recommended dose had remarkably increased the concentration of N, P, K, content in leaf P and K content in tuber. However, inoculation of G. fasciculatum (AMF culture No 3) had shown higher values for nutrient concentration, and it was statistically on par with inoculation of G. fasciculatum with P nutrition at 50 per cent and N and K at recommended dose. Uptake of NPK in leaf, stem and tuber was studied for this experiment which showed that inoculation of G. fasciculatum (AMF culture No 3) had higher values. Hence G. fasciculatum (AMF culture No 3) can be recommended for inoculation in cassava and the application of P fertilizer can be reduced to 50 per cent of the recommended dose for realizing maximum tuber yield and quality.